2017
DOI: 10.11648/j.ijnfs.20170601.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palm Oil Consumption on Lipidic and Lipidoproteinic Profiles in Patients Suffering from Ischemic Heart Pathologies

Abstract: Abstract:Because of its content of saturated fatty acids, palm oil is often considered as being atherogenic nutritionally, and would therefore purveyor of certain diseases including cardiovascular disease. The present study was conducted to assess changes in the lipid profile and lipoprotein of patients with ischemic heart, consumers versus non-consumers of palm oil. The study involved 120 patients enrolled at the Cardiology Institute of Abidjan, divided into 3 groups. Group 1 consisted of 50 patients consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This study also indicated that consumption of this oil decreased serum levels of triglycerides and LDL cholesterol but increased HDL cholesterol. Another study carried out on 120 subjects suffering from ischemic heart disease reported no disturbance of lipid and lipoprotein parameters with these subjects who consumed palm oil after four weeks (Mondé et al, 2017). Several other works of our team on the benefits of palm oil have been carried out for the most part in hypertensive, obese, diabetic, cancerous subjects or suffering from ischemic cardiopathies (Djohan et al, 2010;Bé ké , 2015;Coulibaly, 2015;Lé ga, 2015;Yapo, 2015;Mondé et al, 2017), but not with healthy subjects.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study also indicated that consumption of this oil decreased serum levels of triglycerides and LDL cholesterol but increased HDL cholesterol. Another study carried out on 120 subjects suffering from ischemic heart disease reported no disturbance of lipid and lipoprotein parameters with these subjects who consumed palm oil after four weeks (Mondé et al, 2017). Several other works of our team on the benefits of palm oil have been carried out for the most part in hypertensive, obese, diabetic, cancerous subjects or suffering from ischemic cardiopathies (Djohan et al, 2010;Bé ké , 2015;Coulibaly, 2015;Lé ga, 2015;Yapo, 2015;Mondé et al, 2017), but not with healthy subjects.…”
Section: Introductionmentioning
confidence: 95%
“…Another study carried out on 120 subjects suffering from ischemic heart disease reported no disturbance of lipid and lipoprotein parameters with these subjects who consumed palm oil after four weeks (Mondé et al, 2017). Several other works of our team on the benefits of palm oil have been carried out for the most part in hypertensive, obese, diabetic, cancerous subjects or suffering from ischemic cardiopathies (Djohan et al, 2010;Bé ké , 2015;Coulibaly, 2015;Lé ga, 2015;Yapo, 2015;Mondé et al, 2017), but not with healthy subjects. Knowing that some apparently healthy subjects have an apprehension about palm oil, we found it interesting to study the impact of palm oil consumption on healthy young people in rural areas in order to see whether there are or not lipid and lipoprotein anomalies related to this consumption.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other authors [15] had shown the antioxidant role of crude palm oil in the lack of oxidative stress in an area deficient in selenium within the country. Furthermore, the study carried out [16], on 120 subjects suffering from ischemic heart disease, consuming palm oil during several weeks period did not report any disturbance of the lipid and lipoprotein parameters in these subjects. The consumption of palm oil in connection with human health is at the core area of several controversies.…”
Section: Introductionmentioning
confidence: 84%
“…According to nutritional recommendations, 15 to 35% of calories in the form of lipids must be provided by any diet per day while the average of the total metabolism for an average adult is 2500 Kcal per day [17]. Regarding oil consumption, the recommended intakes were calculated as previously described [16]. In the study area, the entire population consumed palm oil either in the refined form or in the raw form or both.…”
Section: Subjects Criteria For Inclusion and Non-inclusion Of Palm Omentioning
confidence: 99%